Y = -3x - 1......so we sub in -3x - 1 in for y in the other equation
2x + 5y = 12
2x + 5(-3x - 1) = 12....now distribute the 5 through the parenthesis
2x - 15x - 5 = 12...add 5 to both sides
2x - 15x = 12 + 5..combine like terms
-13x = 17...divide both sides by -13
x = -17/13
now sub in -17/13 for x in the other equation
y = -3x - 1
y = -3(-17/13) - 1
y = 51/13 - 1
y = 51/13 - 13/13
y = 38/13
so the solution is (-17/13, 38/13)
Answer:
1.0105
Step-by-step explanation:
93/5 is equal to 9.6,and 92/4 is equal to 9.5,so 9.6/9.5 is 1.01
fraction form is 1 1/100
Mark me brainliest if this helped:D
Answer:
1/36
Step-by-step explanation:
If a cube rolls and it landed on one it’s 1/6 if u rolled he same cube and got one too then it’s still 1/6 so now u just multiply them
Hope this helps